Efeitos renais e cardiovasculares da infusão de dopamina e da solução de cloreto de sódio a 7.5%. Estudo experimental em cães com restrição hídrica - Verderese, Marisa Aparecida Lima; Vianna, Pedro Thadeu Galvão [UNESP]; Ganem, Eliana Marisa; Vane, Luiz Antonio (My University, 2003)
BACKGROUND AND OBJECTIVES: Dopamine infusion for renal protection is controversial. This study aimed at observing the effects of dopamine, hypertonic solution and the association of both in dogs with water restriction, emulating preoperative fast. METHODS: The following renal function parameters were studied in 32 dogs anesthetized with sodium pentobarbital and fentanyl: effective renal plasma flow (sodium paraaminohippurate clearance), glomerular filtration rate (creatinine clearance), sodium, potassium and osmolar clearance, sodium and potassium fractional excretion and renal vascular resistance. Cardiovascular parameters were: mean blood pressure, heart rate, inferior vena cava pressure, cardiac index, hematocrit and peripheral vascular resistance index. Animals were randomly distributed in four experimental groups: Group 1 - G1 (n = 8) - control group; Group 2 - G2 (n = 8) - dopamine infusion (2 μg.kg-1.min-1); Group 3 - G3 (n = 8) - 7.5% sodium chloride (2 ml.kg-1) and Group 4 - G4 (n = 8) - association of dopamine (2 μg. kg-1.min-1) and 7.5% sodium chloride (2 ml.kg-1). Groups underwent four experimental stages lasting 30 minutes each, and involving moments M1, M2, M3 and M4. RESULTS: Dopamine group (G2) had mean blood pressure, renal vascular resistance and potassium excretion decrease. Hypertonic sodium chloride group (G3) had cardiac index, urinary volume, sodium and potassium clearance, sodium and potassium urinary excretion and sodium fractional excretion increase. Group receiving the association of hypertonic solution and dopamine (G4) had heart rate, cardiac index, effective renal plasma flow and sodium urinary excretion increase; there has also been systemic vascular resistance and plasma potassium index decrease. CONCLUSIONS: Our conclusion was that hypertonic sodium chloride solution was able to improve hemodynamic conditions and, as a consequence, renal function of dogs under 12-hour water restriction. The same was not true for 2 μg.kg -1.min-1 dopamine which, in a similar situation, has not increased diuresis and sodium excretion.
Renal and cardiovascular effects of dopamine and 7.5% Sodium chloride infusion. Experimental study in dogs with water restriction
Keywords: Animal, dog; Drugs, adrenergic: dopamine; Renal system: function; Volume status: expansion, 7.5% sodium chloride